Pemberdayaan Ibu Bayi Dan Balita Dalam Pemberian MP-ASI T3 (Tepat Komposisi, Tepat Cara Pembuatan, Tepat Waktu Dan Takaran Pemberian) Untuk Optimalisasi Tumbuh Kembang Bayi Balita Dalam Pencegahan Stunting Di Posyandu Teratai Kelurahan Batu IX - Ridayani, Rita; Batubara, Kartika Sri Dewi; Marella, Marella (Borneo Community Health Service Journal, 2025)
Based on data from the Indonesian Nutrition Status Survey, the prevalence of stunting in the Riau Islands is 17.6%. Referring to data from the 2022 Indonesian Nutrition Status Survey, the stunting rate in Tanjungpinang City dropped from 18.8 percent in 2021 to 15.7 percent in 2022, meaning that it still has to be able to drop by 1.7 percent in order to meet the national target of 14 percent. One of the factors causing stunting in the Batu IX village area is the lack of knowledge and skills of mothers of babies aged 0 - 24 months about how to MP-ASI. The purpose of community service is to increase the knowledge of mothers of babies 0-24 months about MP-ASI T3 (Right Composition, Right Way of Delivery, Right Time and Dosage of Feeding) and the technicalities of its manufacture. The target partners are all mothers of babies aged 0-24 months in the Batu IX Posyandu Teratai Village area with a total of 25 people. The implementation method in this community service activity is the provision of counseling and education to improve mothers' skills on stunting prevention efforts through the practice of making appropriate MP-ASI. The results of the mothers who attended were very enthusiastic and there was an increase in the knowledge of mothers of babies aged 0-24 months about stunting prevention through the practice of making MP-ASI properly